1990
DOI: 10.1183/09031936.93.03090991
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aminophylline on function and intracellular pH of the rat diaphragm

Abstract: We studied the effect of aminophylline on twitch tension (TT) and intracellular pH (pHi) in isolated rat diaphragm strips that were fatigued, hypercapnic, or hypoxic. Superfused muscles were directly stimulated at 0.5 Hz. The pHi was measured from distribution volumes of dimethyl-oxazolidinedione. Fatigue was induced by intermittent tetanic stimulation. Hypercapnia and hypoxia were produced by altering superfusate carbon dioxide tension (PCO2) or oxygen tension (PO2). Aminophylline (1.0 mmol.l-1) reversed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Current tibial components consist of two main material options, all-polyethylene tibial components and metal-backed tibial components, which differ in material and component method, resulting in differences in prosthesis-bone and component-component stresses. It was found that while a significant increase in measured strain was observed for both the all-polyethylene and metal-backed tibial components in the simulated load distribution, the all-polyethylene tibial component showed a more pronounced stress rise at the proximal tibia ( Small et al, 2010 ). Brihault et al (2016) compared the stress distribution and fretting of tibial plateau prostheses made of different materials when the knee joint flexed 120°.…”
Section: Application Of Fea In Tkamentioning
confidence: 98%
See 1 more Smart Citation
“…Current tibial components consist of two main material options, all-polyethylene tibial components and metal-backed tibial components, which differ in material and component method, resulting in differences in prosthesis-bone and component-component stresses. It was found that while a significant increase in measured strain was observed for both the all-polyethylene and metal-backed tibial components in the simulated load distribution, the all-polyethylene tibial component showed a more pronounced stress rise at the proximal tibia ( Small et al, 2010 ). Brihault et al (2016) compared the stress distribution and fretting of tibial plateau prostheses made of different materials when the knee joint flexed 120°.…”
Section: Application Of Fea In Tkamentioning
confidence: 98%
“…This strategy has the advantages of causing less injury and allowing quick recovery ( Scott and Santore, 1981 ; Berend et al, 2005 ). However, UKA is a technically demanding surgical method, and attention must be paid to the size of the components, the osteotomy and postoperative alignment because overcorrection or overloosening may lead to adverse results, these include primarily bearing dislocations (in mobile-bearing designs), aseptic mechanical loosening, polyethylene wear (in fixed-bearing designs), progression of osteoarthritis in unreplaced compartments, periprosthetic fractures and unexplained pain ( Shee et al, 1990 ; Kim et al, 2016 ). Resulting in a typical 10-year survival rate of 80% to 85% for the prosthesis ( Crawford et al, 2020 ), and ways to reduce these adverse events to improve prosthesis longevity need to be continuously explored.…”
Section: Application Of Fea For Alignment In Ukamentioning
confidence: 99%